2010
DOI: 10.5047/eps.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Remotely triggered seismicity in north China following the 2008 M w 7.9 Wenchuan earthquake

Abstract: We conduct a systematic survey of remote triggering of earthquakes in north China following the 2008 M w 7.9 Wenchuan earthquake. We identify triggered earthquakes as impulsive seismic energies with clear P and S arrivals on 5 Hz high-pass-filtered three-component velocity seismograms during and immediately after the passage of teleseismic waves. We find clearly triggered seismic activity near the Babaoshan and HuangzhuangGaoliying faults southwest of Beijing, and near the aftershock zone of the 1976 M w 7.6 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Dynamic triggering has subsequently been shown to occur after the passing of the waves from large earthquakes, for example, the 2002 Denali event ( M w = 7.9) [ Eberhart‐Phillips et al , 2003; Gomberg et al , 2004; Pankow et al , 2004; Prejean et al , 2004; Hough , 2007; Jiang et al , 2010], and the 2004 Sumatra event ( M w = 9.1) [ West et al , 2005; Velasco et al , 2008] earthquakes. While remotely triggered seismicity is mostly found in active plate boundary regions [e.g., Gomberg et al , 2004; Brodsky and Prejean , 2005; Hill and Prejean , 2007]; recently, several studies have shown that remote triggering could also occur in intraplate regions with relatively low background seismicity [ Hough et al , 2003; Hough , 2007; Peng et al , 2009]. Indeed, Velasco et al [2008] studied 15 large events and showed that 12 of them had some evidence of dynamic triggering and their occurrence was virtually independent of tectonic province.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic triggering has subsequently been shown to occur after the passing of the waves from large earthquakes, for example, the 2002 Denali event ( M w = 7.9) [ Eberhart‐Phillips et al , 2003; Gomberg et al , 2004; Pankow et al , 2004; Prejean et al , 2004; Hough , 2007; Jiang et al , 2010], and the 2004 Sumatra event ( M w = 9.1) [ West et al , 2005; Velasco et al , 2008] earthquakes. While remotely triggered seismicity is mostly found in active plate boundary regions [e.g., Gomberg et al , 2004; Brodsky and Prejean , 2005; Hill and Prejean , 2007]; recently, several studies have shown that remote triggering could also occur in intraplate regions with relatively low background seismicity [ Hough et al , 2003; Hough , 2007; Peng et al , 2009]. Indeed, Velasco et al [2008] studied 15 large events and showed that 12 of them had some evidence of dynamic triggering and their occurrence was virtually independent of tectonic province.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitudes of earthquakes triggered remotely by the passage of seismic waves are generally small (M < ~4) (e.g., Miyazawa et al 2005;Miyazawa 2011;Peng et al 2010;Yukutake et al 2013). Thus, studying the Oita earthquake could advance our fundamental understanding of the triggering processes of large earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…These values correspond to peak dynamic stresses of ≥0.09 MPa. The stress threshold therefore is in the range 0.03–0.09 MPa, which lies at the lower end of the range of peak dynamic stresses observed worldwide spanning 0.01–0.5 MPa [ Brodsky et al ., ; Prejean et al ., ; Husen et al ., ; Pankow et al ., ; Peng et al ., ]. This suggests that triggering thresholds in the compressional regime of the Southern Alps are of the same order as those in transtensional and extensional settings, where triggering has been observed previously.…”
Section: Discussionmentioning
confidence: 99%